Zero Waste Perspective in the Implementation of Good Governance in Mataram City - Rahmi Sri Ramadhani; Susi Retna Cahyaningtyas; Siti Atikah (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2022)
Waste is an important issue in good governance management. Zero waste is a visionary concept that can be applied in waste management and the city environment. Waste and environmental management can be indicators of good governance. This research is a literature review of planning documents and regional regulations in Mataram City. In analyzing the data, it will use content analysis by using leximancer in processing the data. The purpose of this study is to identify the zero waste perspective that is applied to environmental planning in the city of Mataram and to map the activities or activities of the waste management program towards zero waste. The results of the research from planning documents and regional regulations, that the environmental concept is in the management theme and has a relationship with the community concept. According to the planning document, the perception of the Mataram city government that the implementation of Zero waste is related to environmental management that has a relationship with the community. In local regulations, the concept of waste is more associated with the concept of water than the concept of waste. The concept of waste with the concept of waste is a concept that is the target of the zero waste program. And lastly, the waste transportation pattern from the Mataram City government still uses the Collect > Disposal > Transport Pattern.